2013
DOI: 10.3109/01612840.2013.785616
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence in the Eastern Part of Iran: A Path Analysis of Risk Factors

Abstract: Intimate partner violence against women is a widespread phenomenon that is the cause of many deleterious health and social consequences. This study examines the impact of some risk factors on partner violence in the eastern region of Iran, using path analysis. The study used a population-based cross sectional study design. In this study, 251 married women who were referred to the health centers were selected through a proportionally stratified and randomized sampling method. Domestic violence was measured usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Studies conducted on the domestic violence in Iran have reported different prevalence rates for each type of violence. In a study on 251 women in the eastern part of Iran, the prevalence of overall violence was 78.1% and the psychological violence (66.5%) was the most prevalent of domestic type (9). In another study in Ahvaz, Iran, the prevalence of violence was 63.8%, with 58.8% of women experiencing psychological abuse (10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted on the domestic violence in Iran have reported different prevalence rates for each type of violence. In a study on 251 women in the eastern part of Iran, the prevalence of overall violence was 78.1% and the psychological violence (66.5%) was the most prevalent of domestic type (9). In another study in Ahvaz, Iran, the prevalence of violence was 63.8%, with 58.8% of women experiencing psychological abuse (10).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the rate of DV in different parts of Iran such as Marivan (32.9%), Sabzevar (78.1%), 6 and Tehran (10.7%). It is estimated that the rate of death resulting from DV among women of over 18 years of age is about 36%.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of IPV recorded in primary care settings varies, depending on the definition and the tools used for screening (Hegarty, Gunn, Chondros, & Small, 2004; Moghaddam Hosseini, Asadi, Akaberi, & Hashemian, 2013; Ruiz-Pérez, Plazaola-Castaño, & del Río-Lozano, 2007; Yut-Lin & Othman, 2008).…”
mentioning
confidence: 99%